WO3 nanorolls self-assembled as thin films by hydrothermal synthesis1. Issue 16 (28th April 2015) - Vankova, S.; Zanarini, S.; Amici, J.; Cámara, F.; Arletti, R.; Bodoardo, S.; Penazzi, N.
<x xml:space="preserve">Abstract</x> We report a novel type of WO3 nanostructure, i.e. nanorolls obtained as a self-assembled thin film on a transparent conductive substrate.